Le scelte in/conciliabili: Roberto Roversi e la neoavanguardia - Lo Monaco, Giovanna (L'ospite ingrato, 2024)
The article explores the relationship between Roversi and the neo-avantgarde, highlighting both points of distance and points of tangency. The reasons behind Roversi’s aversion to the neo-avantgarde are traced through his articles, but it is also pointed out the contrast between his polemical statements and his works of the 1960s, in which he makes extensive use of quote montage, a cardinal technique of avant-garde texts. This affinity is analysed by examining Le descrizioni in atto and Registrazione di eventi: the analysis shows how the apparent similarity of techniques conceals different procedures and reasons, but also how the avant-garde constitutes an example that Roversi takes into account in his search for a literature capable of grasping the problems of the present.